1998
DOI: 10.1038/bjc.1998.302
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble interleukin-2 receptor level as a prognostic indicator in gastric cancer

Abstract: Summary T lymphocytes, activated by interleukin 2 during an anti-tumour response, release soluble interleukin 2 receptors (slL-2R) into the bloodstream. We analysed the prognostic value of the serum slL-2R level in gastric cancer. Serum concentration of slL-2R in 96 gastric cancer patients and 100 healthy control subjects' was measured by enzyme-linked immunosorbent assay. All survivors were followed for more than 50 months. Serum slL-2R level was considered with respect to prognosis, clinicopathological facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The multivariate-adjusted HRs and 95% CIs were directly obtained from 20 studies [38,39,40,24,41,13,25,42,20,43,21,44,45,46,47,37,48,49,29,50]. Based on the multivariate-adjusted HRs, the meta-analyses were performed in terms of OS, DSS and DFS.…”
Section: Resultsmentioning
confidence: 99%
“…The multivariate-adjusted HRs and 95% CIs were directly obtained from 20 studies [38,39,40,24,41,13,25,42,20,43,21,44,45,46,47,37,48,49,29,50]. Based on the multivariate-adjusted HRs, the meta-analyses were performed in terms of OS, DSS and DFS.…”
Section: Resultsmentioning
confidence: 99%
“…Serum levels of this peptide have been estimated in many disease entities including malignancies, diseases of autoaggression and inflammation/infectious-based processes, where sIL-2R serum concentration frequently correlated with disease severity (De Rie et al 1996, Itoh et al 1998, Kami et al 2000, Kapp et al 1988, Matsumoto et al 1998, Nakata et al 1998, Niitsu et al 2001, Spadaro et al 2001, Suenaga et al 1998, Tartour et al 2001, Vonderheid et al 1998). Monitoring of sIL-2R serum levels is a useful method for the assessment of disease intensity, efficacy of provided treatment, and for prediction of further illness course.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies in various solid tumor cases have also shown sIL-2R to be an adverse prognostic feature, especially in patients with nasopharyngeal cancer [34,35], colorectal cancer [36,37], breast cancer [38], ovarian cancer [39][40][41], gastric cancer [42,43], lung cancer [44,45] and leukemia [46,47], respectively. IL-2 has been introduced as a cancer treatment since 1992.…”
Section: Interleukinmentioning
confidence: 71%